2004
DOI: 10.1097/00019501-200405000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Repeated epicardial coronary artery endothelial injuries lead to a global spontaneous coronary artery spasm

Abstract: Epicardial coronary artery endothelial injury may induce spontaneous vasospasticity in the downstream coronary microvessels as well as in the denuded portion, suggesting functional abnormality through the entire coronary arterial tree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…36) They also showed that the levels of 5-HT1B receptor mRNA of coronary arteries are increased compared with those of brain arteries in WHHL rabbits, indicating a difference in receptor number among different vascular beds. Together with their observation, we can speculate Finally, it would be expected from the results of both the present and previous studies that the coronary artery is highly susceptible to mechanical stress, 37) as well as to various noxious stimuli such as hyperlipidemia and hypertension. Moreover, atherosclerotic progression, vascular remodeling, and regulation of vascular tone by various vasoactive substances following repeatedly induced intimal injury might be altered in a vessel-specific manner, although the direct clinical application of the present results must be considered carefully because of the species differences.…”
Section: Alterations Of Responses To Various Vasoactive Agentssupporting
confidence: 81%
“…36) They also showed that the levels of 5-HT1B receptor mRNA of coronary arteries are increased compared with those of brain arteries in WHHL rabbits, indicating a difference in receptor number among different vascular beds. Together with their observation, we can speculate Finally, it would be expected from the results of both the present and previous studies that the coronary artery is highly susceptible to mechanical stress, 37) as well as to various noxious stimuli such as hyperlipidemia and hypertension. Moreover, atherosclerotic progression, vascular remodeling, and regulation of vascular tone by various vasoactive substances following repeatedly induced intimal injury might be altered in a vessel-specific manner, although the direct clinical application of the present results must be considered carefully because of the species differences.…”
Section: Alterations Of Responses To Various Vasoactive Agentssupporting
confidence: 81%
“…From our previous report 32) , it is likely that microvessels may more easily acquire heightened sensitivity to various pathological stimuli than the large coronary artery and that global spontaneous coronary spasm, including downstream microvessels, might finally occur in this model. As the downstream coronary microvessel is never directly damaged during our experimental procedure, abnormal stimuli produced in the epicardial coronary artery may induce microvascular spasm.…”
Section: Study Limitationsmentioning
confidence: 77%
“…1). 23) Through this examination, we found that this model is suitable as a global spontaneous coronary artery spasm model. This model in- Fig.…”
Section: Development Of a Pig Coronary Artery Spasm Modelmentioning
confidence: 89%
“…We have developed such a model in the conscious and unrestrained state using repeated coronary artery endothelial injury, 23,24) which may be linked to vascular smooth muscle hypercontraction ; this type of injury is likely to occur repeatedly over the course of a lifetime as a result of local shear forces and various risk factors (such as hypercholesterolemia, diabetes mellitus, and hypertension). 9) Using this original spasm model, we investigated the mechanism of coronary vasospasm in which impaired endothelial functioning leads to heightened vascular smooth muscle reactivity and provokes intense conduit coronary artery constriction; we also examined the possibility of therapeutic agents such as antioxidants, β1 -blockers, and endothelin type -A antagonist 25 -28) as therapeutic approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation